Penggunaan Ekspresi Regular dalam Meningkatkan Efisiensi Pencarian Produk pada Aplikasi E-Commerce - Kurnia Meiliyani; Alfah Alfah; Nabila Awalia; Tedy Setiadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Product search is one of the important features in e-commerce applications to provide an optimal user experience. This research discusses the implementation of regular expressions as a method to improve the efficiency of product search. With this approach, the system can match string patterns more flexibly, even when there are variations in user input, such as misspellings or inconsistent formatting. The results show that the application of regular expressions can reduce search time by 30% and improve keyword matching accuracy by 95% compared to traditional search methods. This research contributes to the development of more advanced search systems for e-commerce applications.